THE ISSUE OF CLAIMS TO MARITIME TRANSPORT OF CARGO - Matura, Ladislav; Sosedova, Jarmila; Slesinger, Jan (Doprava a spoje, 2009)
This article discusses the context of liability of carrier for the carriage of cargo, resulting from the Hague - Visby Rules. However, also discussed the importance of keeping the documents accompanying the cargo, which may affect this and protect the carrier. The incidence of damage cargo are one of the consequences of neglecting the care of cargo. Examples are those occurring in the damage with an indication of further action to address complaints incurred by the transfer of cargo.